Interview with Dr. Ole Skovmose - Olga Castiblanco (Universidad Distrital Francisco José de Caldas, 2022)
Professor emeritus at the Department of Culture and Learning at Aalborg University, Denmark. He develops his research from the perspective of critical mathematics education. He studies the political dimension of mathematical knowledge, and analyses the mechanisms of power as related to bringing mathematics in action. His work contributes to developing central concepts of critical mathematics education (landscapes of investigation, mathematics in action, close-ups of students and the ghetto) without forgetting the per- manent relationship with its practical possibilities. He has published several books, including Towards a Philosophy of Critical Mathematics Education, translated into Spanish, Dialogue and Learning in Mathematics Education (together with Helle Alrø), Traveling Through Education, In Doubt, Critique as Uncertainty, Students' Foregrounds, and Connecting Humans With Equations (together with Ole Ravn)